2016
DOI: 10.1037/a0039139
|View full text |Cite
|
Sign up to set email alerts
|

Developing and investigating the use of single-item measures in organizational research.

Abstract: The validity of organizational research relies on strong research methods, which include effective measurement of psychological constructs. The general consensus is that multiple item measures have better psychometric properties than single-item measures. However, due to practical constraints (e.g., survey length, respondent burden) there are situations in which certain single items may be useful for capturing information about constructs that might otherwise go unmeasured. We evaluated 37 items, including 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
431
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(444 citation statements)
references
References 76 publications
6
431
0
7
Order By: Relevance
“…Earlier studies have demonstrated that multiple-item measures can often be validly replaced by singleitem measures (Elo, Leppänen, & Jahkola, 2003;Fisher, Matthews, & Gibbons, 2016;Van Hooff, Geurts, Kompier, & Taris, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies have demonstrated that multiple-item measures can often be validly replaced by singleitem measures (Elo, Leppänen, & Jahkola, 2003;Fisher, Matthews, & Gibbons, 2016;Van Hooff, Geurts, Kompier, & Taris, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…We used single-item measures instead of multiple-item scales to measure social capital. While some scholars argue for the practical virtues of single-item measures [112,113], future research may try multiple-item measures to better operationalize each dimension of social capital and to enhance reliability. In addition, we did not examine whether other organizational factors limited the positive impact of social capital on corporate innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although previous studies have demonstrated one item measures to be valid substitutes for longer scales (Drolet & Morrison, 2001;Elo et al, 2003;Fisher, Matthews, & Gibbons, 2016;Kinnunen et al, 2011) future research may benefit from using multiple item measures for lunchtime recovery and recovery experiences. Third, a further limitation concerning the measures is that our study relies solely on self-report measures and may therefore suffer from common method bias.…”
Section: Limitations Strengths and Suggestions For Future Studiesmentioning
confidence: 99%